Global Warming and Social Innovation : the Challenge of a Climate Neutral Society. - Kok, Marcel (Earthscan, 2002)
Societies need to reduce emissions of greenhouse gases by 80 per cent in order to counter the risks of climate change. This study envisions a climate neutral society - one where the output of polluting gases is minimised by social innovations set up in households by local authorities through developments in information and communications technologies and dematerialization and through the shift towards product service systems and emissions trading. The work discusses the possibilities for steering and orchestrating this long-term transition towards a climate-friendly society mapping paths throu.